Meta Analisis Kemampuan Literasi Sains pada Mata Pelajaran Fisika - Langgeng Nitya Mazidah; Iwan Permana Suwarna (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Science literacy skills need to be mastered by every individual in the 21st century. Science literacy is a skill in responding to world developments based on science and technology. Physics is a subject related to nature. Science and physics literacy are interrelated. This study aims to determine the science literacy skills in Indonesia in physics subjects and to find out the factors that influence scientific literacy abilities. This is a meta-analysis using a literature study research method with PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) references. The study results showed that science literacy skills had an average score of 55.31 with a moderate category. The highest score with a score of 82 while the lowest score with a score of 27.5. Factors that influence scientific literacy skills include online learning, learning motivation, and appropriate and effective learning strategies, the quality of teachers and inadequate facilities. Based on the results of the study, it can be concluded that science literacy skills need to be further developed to obtain high-quality human resources.